Abstracts of the 24th international isotope society (UK group) symposium: synthesis and applications of labelled compounds 2015. (18th March 2016) - Aigbirhio, F. I.; Allwein, S.; Anwar, A.; Atzrodt, J.; Audisio, D.; Badman, G; Bakale, R.; Berthon, F.; Bragg, R.; Brindle, K. M.; Bushby, N.; Campos, S.; et al.
Meeting Summary: The 24th annual symposium of the International Isotope Society's United Kingdom Group took place at the Møller Centre, Churchill College, Cambridge, UK on Friday 6th November 2015. The meeting was attended by 77 delegates from academia and industry, the life sciences, chemical, radiochemical and scientific instrument suppliers. Delegates were welcomed by Dr Ken Lawrie (GlaxoSmithKline, UK, chair of the IIS UK group). The subsequent scientific programme consisted of oral presentations, short 'flash' presentations in association with particular posters and poster presentations. The scientific areas covered included isotopic synthesis, regulatory issues, applications of labelled compounds in imaging, isotopic separation and novel chemistry with potential implications for isotopic synthesis. Both short‐lived and long‐lived isotopes were represented, as were stable isotopes. The symposium was divided into a morning session chaired by Dr Rebekka Hueting (University of Oxford, UK) and afternoon sessions chaired by Dr Sofia Pascu (University of Bath, UK) and by Dr Alan Dowling (Syngenta, UK). The UK meeting concluded with remarks from Dr Ken Lawrie (GlaxoSmithKline, UK).